Vanuatu : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Alternate Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report, 2009)
The staff report for Vanuatu's 2009 Article IV Consultation discusses economic developments and policies. Vanuatu is well placed to take countercyclical measures should growth slow more than expected. Although close monitoring of banks is necessary given the rapid growth in the private sector credit last year, the wide differential in policy rates between Vanuatu and its major trading partners suggest that there is some scope for monetary easing if things deteriorate more than expected.